2017
DOI: 10.1111/tpj.13578
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting virulence function from recognition: cell death suppression in Nicotiana benthamiana by XopQ/HopQ1‐family effectors relies on EDS1‐dependent immunity

Abstract: Many Gram-negative plant pathogenic bacteria express effector proteins of the XopQ/HopQ1 family which are translocated into plant cells via the type III secretion system during infection. In Nicotiana benthamiana, recognition of XopQ/HopQ1 proteins induces an effector-triggered immunity (ETI) reaction which is not associated with strong cell death but renders plants immune against Pseudomonas syringae and Xanthomonas campestris pv. vesicatoria strains. Additionally, XopQ suppresses cell death in N. benthamiana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 49 publications
(127 reference statements)
3
24
0
Order By: Relevance
“…It is known that N . benthamiana recognizes XopQ, via the R protein Roq1 (Schultink et al, ), and initiates ETI responses (Schwartz et al ., ; Adlung et al ., ; Adlung and Bonas, ). Although the XopQ‐triggered stromule induction is impressive it is not surprising given the known link between ETI and increased stromule frequencies (Caplan et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that N . benthamiana recognizes XopQ, via the R protein Roq1 (Schultink et al, ), and initiates ETI responses (Schwartz et al ., ; Adlung et al ., ; Adlung and Bonas, ). Although the XopQ‐triggered stromule induction is impressive it is not surprising given the known link between ETI and increased stromule frequencies (Caplan et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…XopQ induced an increase in stromule frequency to 56%, whereas XopL caused a dramatic reduction to 2% stromule frequency (n = 2 plants). It is known that N. benthamiana recognizes XopQ, via the R protein Roq1 (Schultink et al, 2017), and initiates ETI responses (Schwartz et al, 2015;Adlung et al, 2016;Adlung and Bonas, 2017). Although the XopQ-triggered stromule induction is impressive it is not surprising given the known link between ETI and increased stromule frequencies (Caplan et al, 2015).…”
Section: Effectors As Molecular Probes For Stromule Dynamicsmentioning
confidence: 99%
“…a,b) might be explained by differences in signalling pathways between HR cell death and other ETI responses. From another viewpoint, it has recently been suggested that the ETI response induced by the RipB homologues XopQ and HopQ1 has severe negative effects on the multiplication of A. tumefaciens as well as on Agrobacterium ‐mediated transient protein expression in N. benthamiana (Adlung and Bonas, ). Therefore, the chlorosis induced by the transient expression of RipB might be caused by the attenuated transient expression of RipB.…”
Section: Discussionmentioning
confidence: 99%
“…The repertoire of T3 effectors of X. campestris pv. vesicatoria comprises more than 35 proteins, among them the AvrBs3 transcription factor, cell death inducers, plant immunity suppressors (Adlung & Bonas, ), or the XopL ubiquitine ligase. The characterisation of the latter reveals an unprecedented role of microtubules in stromule extension and dynamics in Nicotiana benthamiana (Erickson, Adlung, Lampe, Bonas, & Schattat, ).…”
Section: Effector‐mediated Subversion Of Host Cellsmentioning
confidence: 99%